4CPS-048 Evaluation of colistimethate sodium (cms) prescriptions for the management of multidrug-resistant gram-negative bacterial infections. (2nd March 2018) - Sadyrbaeva, S; García-Fumero, R; Sánchez-Argaiz, M; Guijarro-Herrera, S; Jiménez-Morales, A; Pasquau, J
Abstract : Background: The emergence of highly-resistant gram-negative bacteria, in particular acinetobacter baumanii pseudomonas aeruginosa, and carbapenem-resistant klebsiella species has been associated with high rates of morbidity and mortality. Therapeutic options for these pathogens are limited. Because of the lack of newer antimicrobial agents, colistimethate sodium (CMS) has been recently reused for the treatment of infections caused by this microorganism. Purpose: The study aimed to assess CMS prescriptions and analyse the occurrence of nephrotoxicity after CMS administration. Material and methods: A retrospective observational study was performed at a tertiary-care university hospital between 1 January 2016 and 31 July 2017 including every patient who had received intravenous CMS for at least 48 hours. Clinical data were obtained from electronic medical records. Only one treatment per patient was considered in the analysis. The following variables were collected: patient characteristics, site of infection, type of microorganism, daily dosage and duration of CMS used and concomitant antimicrobial treatment, and laboratory data: serum creatinine (at day 1 and during the therapy), albumin, haemoglobin and leukocytes. Nephrotoxicity was defined as at least two consecutive serum creatinine measurements with an increase of 0.5 mg/dl from the baseline after 2 or more days of CMS therapy. Results: A total of 75 patients received CMS therapy, 53 (70.7%) were male. The median age of the patients was 69 (IQR, 57–79) years, Charlson index 2 (1–3)and eGFR (CKD-EPI) was 91. 1 (IQR, 78.9–113.2) ml/min/1.73 m 2 . Nephrotoxicity developed in 35 (46.7%) patients. The median onset time for nephrotoxicity was 7 days (IQR, 3–12). Patients with nephrotoxicity were older than those without it (74 years vs 64 years, p=0.025) and had lower median serum albumin and haemoglobin levels 2.9 vs 3.1 (p=0.501) and 9.4 vs 10.1 (p=0.069) respectively. The median daily dose of CMS was 9 MU, the loading dose was administered in 25 (33.3%) patients. In 24 patients (32.0%) the dosage was adjusted according to eGFR. The median duration of treatment was 10 (IQR, 6–15) days. Bloodstream infections occurred in 19 (25.3%) patients. Principal infectious sources were: respiratory (38.7%), urinary (25.3%) and skin and soft tissue (17.3%). Pathogens were A. baumanii 73.3%, P. aeruginosa 17.3% and carbapenem-resistant enterobacteriaceae 10.7%. In 41 patients (54.7%) CMS was administered in combination therapy. Causes for the end of treatment were clinical resolution (56.0%), change to other (13.3%), toxicity (13.4%) and death (17.3%). Conclusion: In conclusion, very low rates of adjustment of the dosage by eGFR were observed. Almost half of the patients developed nephrotoxicity due to the CMS therapy, which was significantly associated with the age of patients. No conflict of interest